PENGABDIAN KEPADA MASYARAKAT DENGAN MELATIH SISWA UNTUK BERBICARA DI DEPAN UMUM PADA SISWA KELAS VII SMP NEGERI 1 SIMANINDO - Simangunsong, Putri Nomenselli Simangunsong (CV. Alfa Pustaka, 2024)
This community service aims to train public speaking skills in grade VII students of SMP Negeri 1 Simanindo. Public speaking skills are a very important ability to be developed from an early age, because they can improve students' confidence, communication skills, and social skills. This activity was carried out through a series of trainings and simulations involving theoretical and practical approaches, with a focus on speaking techniques, anxiety management, and how to convey ideas clearly and interestingly. The methods used are lectures, interactive discussions, and live exercises in the form of group presentations. The results of this activity showed a significant improvement in students' speaking skills, which was reflected in their confidence in speaking in front of the class and the positive response from participants to the material presented. It is hoped that this activity can be the basis for the development of students' communication skills in the future, as well as have a positive impact on improving students' academic and social achievements.